2020
DOI: 10.3389/fimmu.2020.00316
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination Against Tuberculosis: Revamping BCG by Molecular Genetics Guided by Immunology

Abstract: Tuberculosis (TB) remains a major health threat. Although a vaccine has been available for almost 100 years termed Bacille Calmette-Guérin (BCG), it is insufficient and better vaccines are urgently needed. This treatise describes first the basic immunology and pathology of TB with an emphasis on the role of T lymphocytes. Better understanding of the immune response to Mycobacterium tuberculosis (Mtb) serves as blueprint for rational design of TB vaccines. Then, disease epidemiology and the benefits and failure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
77
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 131 publications
(183 reference statements)
0
77
0
Order By: Relevance
“…These deletions alter the expression of different Mycobacterium virulence factors (18)(19)(20)(21). The differential expression of these molecules leads to the induction of different immune responses when exposed to an M. tuberculosis infection or BCG vaccination (8,22). Trained immunity induction has only been described for BCG vaccination (13)(14)(15)23).…”
Section: Introductionmentioning
confidence: 99%
“…These deletions alter the expression of different Mycobacterium virulence factors (18)(19)(20)(21). The differential expression of these molecules leads to the induction of different immune responses when exposed to an M. tuberculosis infection or BCG vaccination (8,22). Trained immunity induction has only been described for BCG vaccination (13)(14)(15)23).…”
Section: Introductionmentioning
confidence: 99%
“…The development of newer vaccines aims at either a new form of recombinant BCG (rBCG) or ones that boosts the conventional BCG vaccine. Several potential rBCG/BCG vaccine candidates with novel adjuvants are currently being evaluated for use in TB prevention in clinical studies [139][140][141][142]. As previously stated, studies using mouse models have indicated the cross-reactive immunity offered by BCG to pulmonary NTM infections caused by M. avium, M. abscessus, and M. kansasii [82,143].…”
Section: Complications Of Ntm Disease Treatmentmentioning
confidence: 95%
“…Weiner Kaufmann, 2020Ag85A, PPE, and pfkB Multistage DNA vaccine, A39 Su et al, 2017Ag85C, MPT5, and HspX rBCG-CMX da Costa et al, 2017 Lipo-AE vaccine formulation with the PolyIC adjuvant Diogo et al, 2019 ESAT-6, CFP-10, TB10.3, AlaDH, Ag85B, PstS1, andHspX ELISPOT assay Chiappini et al, 2012 38kD, ESAT-6, and CFP-10 Multiple-antigen detection assay Dai et al, 2017 CFP-10 and ESAT-6 Electrochemical-based SPCE Bakhori et al, 2020 ESAT-6, 6-kDa early secretory antigenic target; CFP, culture filtrate protein; rBCG, recombinant bacille Calmette-Guérin; ELISPOT, enzyme-linked immunospot assay; CMX, Ag85C-MPT51-HspX fusion protein; SPCE, screen-printed carbon electrode. For further details on Mycobacterium tuberculosis (Mtb) proteins, see the database: http://www.tbdb.org and http://tuberculist.epfl.ch immune response to the Ag85B antigen, but a weak immune response to ESAT-6 (Diogo et al, 2019).…”
Section: Id93mentioning
confidence: 99%
“…In LTBI, the Mtb reproduces inside the cellular host, developing a complex relationship that might progress to active TB infection (ATBI). Because TB is one of the top 10 causes of death from an infectious agent, prevention strategies and the development of better vaccines have been pursued (Kaufmann, 2020). Also, about 2000 million people worldwide have LTBI that might progress to ATBI at any time .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation